The proximate regulation of prosocial behaviour: towards a conceptual framework for comparative research - Kathrin S. Kopp; Patricia Kanngiesser; Rahel K. Brügger; Moritz M. Daum; Anja Gampe; Moritz Köster; Carel P. van Schaik; Katja Liebal; Judith M. Burkart (Animal Cognition)
Abstract Humans and many other animal species act in ways that benefit others. Such prosocial behaviour has been studied extensively across a range of disciplines over the last decades, but findings to date have led to conflicting conclusions about prosociality across and even within species. Here, we present a conceptual framework to study the proximate regulation of prosocial behaviour in humans, non-human primates and potentially other animals. We build on psychological definitions of prosociality and spell out three key features that need to be in place for behaviour to count as prosocial: benefitting others, intentionality, and voluntariness. We then apply this framework to review observational and experimental studies on sharing behaviour and targeted helping in human children and non-human primates. We show that behaviours that are usually subsumed under the same terminology (e.g. helping) can differ substantially across and within species and that some of them do not fulfil our criteria for prosociality. Our framework allows for precise mapping of prosocial behaviours when retrospectively evaluating studies and offers guidelines for future comparative work.